Attachment and mentalization and their association with child and adolescent eating pathology: A systematic review. Issue 4 (22nd December 2015) - Jewell, Tom; Collyer, Hannah; Gardner, Tessa; Tchanturia, Kate; Simic, Mima; Fonagy, Peter; Eisler, Ivan
ABSTRACT: Objective: Insecure attachment and mentalizing difficulties have been associated with eating pathology in adulthood. However, it is unclear whether eating pathology is associated with attachment or mentalization in children. The aim of this study is to systematically review the literature in this emerging field. Method: Electronic databases were used to search for articles. Results: Twenty‐two studies were identified. In the 15 studies investigating attachment, an association with eating pathology was found in all studies. Mentalizing difficulties and eating pathology were found to be correlated in the seven studies which examined their association. Discussion: In keeping with the adult literature, cross‐sectional studies of children and adolescents consistently report associations with eating pathology. There is some evidence from prospective studies that insecure attachment may be a risk factor for the development of eating pathology in adolescence. The literature on mentalization and eating pathology suggests that adolescents with anorexia nervosa may have difficulties in recognizing emotions. Further research using clinical samples and well‐validated measures of attachment and mentalization are required to shed further light on this area.